Daily administration of Sake Lees (Sake Kasu) reduced psychophysical stress-induced hyperalgesia and Fos responses in the lumbar spinal dorsal horn evoked by noxious stimulation to the hindpaw in the rats. Issue 1 (2nd January 2020) - Shimizu, Shiho; Nakatani, Yosuke; Kakihara, Yoshito; Taiyoji, Mayumi; Saeki, Makio; Takagi, Ritsuo; Yamamura, Kensuke; Okamoto, Keiichiro
ABSTRACT: We tested whether Sake Lees (SL) had inhibitory effects on hyperalgesia in the hindpaw under psychophysical stress conditions. Male rats were subjected to repeated forced swim stress treatments (FST) from Day −3 to Day −1. Intraperiotoneal administration of SL which contained low concentration of ethanol (SLX) was conducted after each FST. On Day 0, formalin-evoked licking behaviors and Fos responses in the lumbar spinal cord (DH) and several areas within the rostral ventromedial medulla (RVM) were quantified as nociceptive responses. FST-induced hyperalgesia in the hindpaw was prevented by repeated SL and SLX treatments. Fos expression was significantly increased in DH and some areas within the RVM under FST, which was prevented by repeated SL or SLX. These findings indicated that daily administration of SL had the potential to alleviate stress-induced hyperalgesia. Graphical abstract: : Modulatory roles of Sake Lees on stress-induced hyperalgesia.